Performance of Single Slope Solar Still with Solar Protected Condenser - Al-Hamadani, Ali Abdulruda Farhan; Shukla, S.K. (Distributed Generation & Alternative Energy Journal, 2013)
To improve the performance of the single slope solar still, an ab- sorber plate with block shaped fins and a Phase Change Material cham- ber (PCM) with slender shaped fins are used. Experimental investiga- tions have been carried out on two solar stills, namely conventional solar still and a modified solar still with PCM. The influence of the depth of water and the mass of PCM on the performance of the modified solar still with PCM has been investigated. The fins were equipped in the basin of the solar still to augment evaporation of the basin water. To enhance the heat transfer between the phase change material and the absorber plate, slender shaped fins were welded on the upper of PCM’s chamber. The condensation of solar still was increased by using a secondary condenser on the shaded side of single slope solar still. The added secondary con- denser was shielded to keep the surface of the condenser cool. It was found that the productivity of the modified solar still in comparison with conventional solar still was enhanced during day and night.